Recent developments in modulating atherogenic lipoproteins. Issue 5 (October 2015) - White, C. Roger; Goldberg, Dennis I.; Anantharamaiah, G.M.
Abstract : Purpose of review: Randomized clinical trials have assessed the effects of several classes of drugs on plasma cholesterol levels in patients with coronary artery disease. Agents including niacin, fibrates and statins significantly lower LDL-cholesterol, but tolerance issues and undesirable side-effects are common. Residual risk may also be present in patients with persistently low HDL-cholesterol despite a reduction in LDL-cholesterol. Recent trials of drugs that increase circulating HDL-cholesterol have also been disappointing. Recent findings: Ongoing efforts target the development of new pharmacotherapies to reduce circulating levels of atherogenic lipoproteins. The goal of this review is to discuss recent advances in the treatment of coronary artery disease and other vascular diseases characterized by an increase in circulating atherogenic lipoproteins. These include the development of inhibitors of ATP citrate lyase and proprotein convertase subtilisin/kexin type 9. We also discuss recent developments in HDL therapy, including the clinical assessment of cholesteryl ester transfer protein inhibitors and apolipoprotein E mimetic peptides. Summary: Several new classes of drug are undergoing clinical evaluation that show promise for atherogenic lipoprotein reduction in patients who are statin intolerant.